Conservation and Restoration of the House of Butehamon 21st Dynasty 1054 BC - The Medinet Habu Temple Precinct (Global Journal of Human-Social Science, 2023)
Understanding the original materials and techniques used in objects not only provides insights into its history of construction but may also shed light on the nature of past and current deterioration problems
Keywords: conservation; archaeology; egyptology; heritage; reintegration; integration; restoration; ancient egypt; art; conservation science